Prematurity and Low Birth Weight in Neonates as a Risk Factor for Obesity, Hypertension, and Chronic Kidney Disease in Pediatric and Adult Age - Grillo, Maria Agostina; Mariani, Gonzalo; Ferraris, Jorge R. (Frontiers in Medicine, 2022)
Low weight at birth may be due to intrauterine growth restriction or premature birth. Preterm birth is more common in low- and middle-income countries: 60% of preterm birth occur in sub-Saharan African or South Asian countries. However, in some higher-income countries, preterm birth rates appear to be increasing in relation to a reduction in the lower threshold of fetal viability. The cutoff is at 22-23 weeks, with a birth weight of approximately 500 grams, although in developed countries such as Japan, the viability cutoff described is 21-22 weeks. There is evidence of the long-term consequences of prenatal programming of organ function and its relationship to adult diseases, such as hypertension (HT), central obesity, diabetes, metabolic syndrome, and chronic kidney disease (CKD). Premature delivery before the completion of nephrogenesis and intrauterine growth restriction leads to a reduction in the number of nephrons that are larger due to compensatory hyperfiltration and hypertrophy, which predisposes to the development of CKD in adulthood. In these patients, the long-term strategies are early evaluation and therapeutic interventions to decrease the described complications, by screening for HT, microalbuminuria and proteinuria, ultrasound monitoring, and renal function, with emphasis on preventive measures. This review describes the effects of fetal programming on renal development and the risk of obesity, HT, and CKD in the future in patients with low birth weight, and the follow-up and therapeutic interventions to reduce these complications.